Sexual activity of Pink-footed Geese Answer brachyrhynchus at a staging area in Iceland - Boyd, H; Fox, A D (Wildfowl, 1992)
On 30 April and 1 May 1991 several of a group of 170 staging Pink-footed Geese feeding near the Bruara, at least 16 km from their nearest known nesting sites, engaged in sexual activities while visiting the river to bathe and drink. Some copulations seemed complete. These activities were contagious, and once elicited similar behaviour by White-fronted Geese sharing the bathing area, though the Greylag Geese in whose territories the activities occurred did not join in.